Thyrotropin and free thyroxine levels and coronary artery disease: cross-sectional analysis of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) - de Miranda,E.J.F. Peixoto (2018)
Data on the association between subclinical thyroid dysfunction and coronary artery disease (CAD) is scarce. We aimed to analyze the association between thyroid function and CAD using baseline data from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). We included subjects with normal thyroid function (0.4-4.0 mIU/L, and normal free thyroxine, FT4, or 0.8 to 1.9 ng/dL), subclinical hypothyroidism (SCHypo; TSH>4.0 mIU/L and normal FT4), and subclinical hyperthyroidism (SCHyper; TSH<0.4 mIU/L and normal FT4) evaluated by coronary computed tomography angiography. We excluded individuals using medications that interfere in thyroid function or with past medical history of cardiovascular disease. Logistic regression models evaluated the presence of CAD, segment involvement score (SIS) >4, and segment severity score (SSS) >4 of coronary arteries as the dependent variables, and quintiles of TSH and FT4 as the independent variables, adjusted for demographical data and cardiovascular risk factors. We included 767 subjects, median age 58 years (IQR=55-63), 378 (49.3%) women, 697 euthyroid (90.9%), 57 (7.4%) with SCHypo, and 13 (1.7%) with SCHyper. No association between TSH and FT4 quintiles and CAD prevalence was noted. Similarly, no association between TSH levels and the extent or severity of CAD, represented by SIS>4 and SSS>4 were seen. Restricting analysis to euthyroid subjects did not alter the results. TSH levels were not significantly associated with the presence, extent, or severity of CAD in a middle-aged healthy population.